Remodeling an existing rare disease registry to be used in regulatory context: Lessons learned and recommendations - Mordenti, Marina; Boarini, Manila; D’Alessandro, Fabio; Pedrini, Elena; Locatelli, Manuela; Sangiorgi, Luca (Frontiers in Pharmacology, 2022)
Disease registries have been individuated as an interesting source of real-world data for supporting regulatory decision-making. In fact, drug studies based on registries cover pre-approval investigations, registry randomized clinical trials, and post-authorization studies. This opportunity has been investigated particularly for rare diseases - conditions affecting a small number of individuals worldwide – that represent a peculiar scenario. Several guidelines, concepts, suggestions, and laws are already available to support in the design or improvement of a rare disease registry, opening the way for the implementation of a registry capable of managing regulatory purposes. The present study aims to highlight the key stages performed for remodeling the existing Registry of Multiple Osteochondromas - REM into a tool consistent with EMA observations and recommendations, as well as to lead the readers through the entire adapting, remodeling, and optimizing process. The process included a variety of procedures that can be summarized into three closely related categories: semantic interoperability, data quality, and governance. At first, we have strengthened interoperability within the REM registry by integrating ontologies and standards for proper data collection, in accordance with FAIR principles. Second, to increase data quality, we added additional parameters and domains, as well as a double check to limit human error to a bare minimum. Finally, we have established a two-level governance that have increased the visibility for the scientific community as well as for patients and carers. In conclusion, our remodeled REM registry fits with most of the scientific community's needs and indications, as well as the best techniques for providing real-world evidence for regulatory aspects.